The influence of manipulating the defensive playing method on team synchrony in association football - Duarte, R.; Travassos, B.; Araujo, D.; Richardson, M. (World Congress of Performance Analysis of Sport IX, 2012)
Successfully performance in Association Football is typically viewed as an expression of a collective synergy between the individual behaviours of each player. However, certain performance constraints, such as the defensive playing method, can influence the way team players synchronise their behaviour. The aim of this study was to analyse how the manipulation of the defensive playing method influences the collective synchrony of football players during performance. Twelve under-17 elite footballers were divided in two teams, with a GK+1+3+1 diamond shape formation, with players assigned to their common positions. Teams performed two small-sided games in a 40 x 42m of pitch size, in which the defensive playing method was manipulated. In the first game both teams used zone defence. In the second game players were paired and teams used man-to-man defence. Positional data from the 10 outfield players were gathered using a Global Positioning System (GPSports, Australia) with a sample rate of 15 Hz. Based on players` movement displacement trajectories, the cluster phase method (Frank & Richardson, 2010) was used to calculate time-series data of team synchrony, as well as the individual synchronisation of each player with the team (employing relative phase analysis). Time-series data of team synchrony is presented in left panel of Figure 1. Mean data showed considerable higher values for zone defence (0.63± 0.24) than for man-to-man defence (0.47±0.21), indicating that zone defence constrained players to enhance the team synchrony of their on-field movement trajectories in space and time. Frequency histogram analyses (right panel of Figure 1) also revealed differences in individual players` synchronisation with the whole team behaviour. Adopting a man-to-man defence implied less attraction for any specific mode of relation and more spread for the entire spectrum of coordination possibilities. Conversely, adopting zone defence promoted higher attraction for relative phase values near in-phase mode of coordination (49.8% between -30 and 30 degrees), suggesting that zone defence seems to result in more aggregated team behaviours with increasing stability in the individual-to-team coordination.